2021
DOI: 10.1161/circulationaha.120.051775
|View full text |Cite
|
Sign up to set email alerts
|

Premature Menopause, Clonal Hematopoiesis, and Coronary Artery Disease in Postmenopausal Women

Abstract: Background: Premature menopause is an independent risk factor for cardiovascular disease in women, but mechanisms underlying this association remain unclear. Clonal hematopoiesis of indeterminate potential (CHIP), the age-related expansion of hematopoietic cells with leukemogenic mutations without detectable malignancy, is associated with accelerated atherosclerosis. Whether premature menopause is associated with CHIP is unknown. Methods: We included po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 60 publications
3
83
0
Order By: Relevance
“…This may be partly explained by an association between CHIP and CVD. On a population level, CHIP has been linked to a greater burden of atherosclerotic vessel disease and a heightened risk of myocardial infarction 50 52 as well as to higher blood levels of the inflammatory marker C-reactive protein 53 . Mouse models of CHIP have demonstrated mechanistic ties between certain common CHIP mutations and accelerated atherosclerosis 50 , 54 , 55 as well as heart failure 56 , 57 .…”
Section: Clonal Haematopoiesismentioning
confidence: 99%
“…This may be partly explained by an association between CHIP and CVD. On a population level, CHIP has been linked to a greater burden of atherosclerotic vessel disease and a heightened risk of myocardial infarction 50 52 as well as to higher blood levels of the inflammatory marker C-reactive protein 53 . Mouse models of CHIP have demonstrated mechanistic ties between certain common CHIP mutations and accelerated atherosclerosis 50 , 54 , 55 as well as heart failure 56 , 57 .…”
Section: Clonal Haematopoiesismentioning
confidence: 99%
“…After 6.9 years of the follow-up period, they identified increased CVD risk (hazard ratio (HR) − 1.27%) in subjects with CHIP mutations (Bick et al [ 20 ]). The other study was performed on postmenopausal women by Honigberg et al [ 21 ]; 11,495 samples (40–70 years) were obtained from UK BioBank and 8111 samples (50–79 years) were obtained from Women’s Health Initiative (WHI). The study reported that among postmenopausal middle-aged women, CHIP was independently associated with incident coronary artery disease (HR associated with all CHIP: 1.36).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, systemic markers of inflammation, including CRP, are higher in post-menopausal women than they are in those who are pre-menopausal [ 150 , 151 ]. It is of note that, in women included in the U.K. Biobank and Womens Health Initiative, the prevalence of CHIP was 60% higher in women with premature menopause compared with those without and the presence of CHIP was independently associated with incident coronary artery disease [ 152 ]. Whether or not the presence of CHIP and early-onset menopause increases the risk of developing HFpEF is unknown.…”
Section: Interplay Between Chip Ageing Inflammation and Hfpefmentioning
confidence: 99%